2022
DOI: 10.1080/13880209.2022.2097700
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin protects against renal interstitial fibrosis in mice by inhibiting the TGF-β/Smad signalling pathway

Abstract: Context Baicalin, a flavonoid extracted from radix scutellariae, possesses various pharmacological effects, including protective effects on renal interstitial fibrosis (RIF), but its possible role and mechanisms have not been fully elucidated. Objective This study explores the protective effects and mechanisms of baicalin on RIF. Materials and methods C57BL/6 male mice were divided into six groups: sham, model, low baicalin, middle baicalin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Meanwhile, KAE attenuates renal injury and reverses phenotypic transformation and collagen accumulation in renal tubular epithelial cells [22]. Baicalin, emodin, chrysophanol, and ferulic acid are potential therapeutic options for delaying renal fibrosis by inhibiting the TGF‐β/Smad signaling pathway [23–26]. Moreover, emodin and chlorogenic acid induce myofibroblast apoptosis by regulating the PI3K/Akt pathway, thereby improving renal tubular interstitial fibrosis [27, 28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, KAE attenuates renal injury and reverses phenotypic transformation and collagen accumulation in renal tubular epithelial cells [22]. Baicalin, emodin, chrysophanol, and ferulic acid are potential therapeutic options for delaying renal fibrosis by inhibiting the TGF‐β/Smad signaling pathway [23–26]. Moreover, emodin and chlorogenic acid induce myofibroblast apoptosis by regulating the PI3K/Akt pathway, thereby improving renal tubular interstitial fibrosis [27, 28].…”
Section: Resultsmentioning
confidence: 99%
“…Baicalin, emodin, chrysophanol, and ferulic acid are potential therapeutic options for delaying renal fibrosis by inhibiting the TGF-β/Smad signaling pathway [23][24][25][26]. Moreover, emodin and chlorogenic acid induce myofibroblast apoptosis by regulating the PI3K/Akt pathway, F I G U R E 3 Continued thereby improving renal tubular interstitial fibrosis [27,28].…”
Section: Qsg Chemical Constituent Analysis In Vitromentioning
confidence: 99%
“…Based on dosage, Baicalin activates TGF‐β/Smad signalling pathway and contributes to renal fibrosis 123 . Although it's not always the case, since a study conducted on mice models of RIF showed opposite results 124 . It was revealed that baicalin acts as an anti‐fibrotic agent in renal fibrosis via suppressing the mentioned pathway 124 …”
Section: Antioxidants As a Modulator Of Tgf‐β/ Smad Pathway In Differ...mentioning
confidence: 99%
“…123 Although it's not always the case, since a study conducted on mice models of RIF showed opposite results. 124 It was revealed that baicalin acts as an anti-fibrotic agent in renal fibrosis via suppressing the mentioned pathway. 124 Table 4 summarizes treatment of renal fibrosis models and cell lines with different antioxidants and their subsequent impact on TGF-β/ SMAD pathway.…”
Section: Renal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation